Z oddali, z bliska - Różycki, Robert (1962- ).; Lévi-Strauss, Claude (1908-2009). (1994)
Recenzja książki: Spojrzenie z oddali / Claude Lévi-Strauss. Warszawa, 1993.
Tytuł nagłówkowy.
Keywords: Książki -- recenzje -- 1990-.